SMALL PROSE OF ROSTISLAV ENDIC AND LES’ MARTOVICH: TYPOLOGY OF CHARACTER - Zalevsca, O. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
In the article traced influencing of humorous and satiric traditions Les’ Martovich in creation of Rostislav Endik, mentioned on the synthesis of categories of tragic and comical in the manner of letter.